Diversity of Microorganisms Hosted by the Albanian Medicinal Plants and the Antimicrobial Effect of the Chemical Compounds Extracted by Them - Troja, E.; Dalanaj, N.; Ceci, R.; Troja, R.; Toska, V.; Mele, A.; Como, A.; Petre, A.; Prifti, D. (IntechOpen, 2012)
None